THE EFFECTS OF COCAINE USE ON THE COURSE AND OUTCOME OF PREGNANCY - Bojanić, Novica; Milenković, Jelena; Obradović, Darija; Bojanić, Jelena; Djindjić, Nataša; Ilić, Stefan (Acta medicae Medianae, 2026)
The epidemic of drug addiction is a significant public health issue worldwide. Through easy availability of cocaine, its use by childbearing women may have deleterious effects on the course and outcome of pregnancy. Cocaine use during pregnancy causes: intrauterine growth retardation, abruptio of placenta, increased frequency of premature birth, premature rupture of the membranes, precipitous labor, meconium-stained amniotic fluid, stillbirth, neonatal necrotizing enterocolitis, neonatal bowel perforation, complete bilateral absence of the diaphragm, neonatal respiratory disorders, neonatal subcutaneous fat necrosis, sudden infant death syndrome, intimal fibromuscular dysplasia of numerous blood vessels, hearing impairment, retinal hemorrhages, fetal or maternal intracranial accident, rupture of the uterus, ruptured tubal ectopic pregnancy, placenta previa, changes in neonatal behavior, neonatal cardiac arrhythmias, various congenital anomalies, maternal myocardial infarction and long QT interval in a parturient. Retrospective studies have shown that intrauterine exposure to cocaine causes major malformations in newborns: congenital heart defects, genitourinary, brain and skull anomalies, absence of limbs, ankyloglossia, hypothalamic hamartoblastoma, and Poland-Möbius syndrome. Some authors suggest that there is a specific fetal cocaine syndrome and a link between the high incidence of autism and exposure to cocaine in utero. Cocaine is a neurobehavioral teratogen, as long-term monitoring of prenatally exposed children has shown deleterious effects of cocaine on their psychophysical development. Cocaine use during pregnancy can result in a wide range of adverse effects on pregnancy and its outcome.